Adherence to Low Carbohydrate Diet in Relation to Chronic Obstructive Pulmonary Disease - Malmir, Hanieh; Onvani, Shokouh; Ardestani, Mohammad Emami; Feizi, Awat; Azadbakht, Leila; Esmaillzadeh, Ahmad (Frontiers in Nutrition, 2021)
Purpose: Data on the link between adherence to a low-carbohydrate diet (LCD) and odds of chronic obstructive pulmonary disease (COPD) are scarce. The current study aimed to investigate the relation between adherence to LCD and COPD in Iranian adults. Methods: In this hospital-based case-control study, we enrolled 84 newly-diagnosed COPD patients and 252 age and sex-matched healthy controls in Alzahra University Hospital, Isfahan, Iran. COPD was defined based on findings of spirometry test (forced expiratory volume in 1 second (FEV1)/forced vital capacity (FVC) < 70% or FEV1 < 80%). Dietary intakes of study participants were assessed using the validated Block-format 168-item FFQ. Data on potential confounders were also collected through the use of a pre-tested questionnaire. Results: Mean age of cases and controls were 57.7 and 55.07 years, respectively. Adherence to LCD was inversely associated with odds of COPD (0.35; 95% CI: 0.16-0.75). This inverse association did not alter after controlling for age, sex, and energy intake (0.42; 95% CI: 0.19-0.93). Adjustments for other potential confounders, including dietary intakes, smoking, and educational status, did not affect these findings; such that those in the highest quintile of LCD score were 64% less likely to have COPD than those in the lowest quintile (OR: 0.36; 95% CI: 0.13-0.99). Conclusion: We found an inverse association between adherence to LCD and odds of COPD. The association remained statistically significant even after taking other potential confounders, including socioeconomic characteristics and dietary intakes into account.